Towards a Psycho-Sociological Understanding of Allah - Bharat Jhunjhunwala (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2021)
It is not possible to determine whether Allah is inside the universe or outside it. While the traditional understanding is that Allah is “outside” the universe; the “inside” understanding is consistent with the Qur’ān as well as the writings of Carl G. Jung, Emile Durkheim, Abraham Maslow, and Philip Goff and can explain the concept and the writ of Allah to the modern mind. We hypothesize that Allah is the name given to the consciousness of every particle in the universe fused into One and called Universal Consciousness. The consciousness is not prior- or after matter but exists in parallel. There is a 2-way give-and-take between Allah and the Universe. The believers have a more direct communication with Allah. Allah rules upon the universe and, at the same time, Allah is constituted of the Collective Consciousness of the same universe. We show this hypothesis is consistent with al-Nūr 24:35 and Sūra al-Ikhlāṣ. This approach can be the foundation on which we can build a concordance between the understandings of Qur’ānic Allah and modern science, thus explain the majesty of Allah to the science-oriented modern mind including the atheists without diluting the spiritual content of the Holy Qur’ān.